2018
DOI: 10.1159/000488393
|View full text |Cite
|
Sign up to set email alerts
|

Basic Research Advances on Pituitary Stem Cell Function and Regulation

Abstract: As a central regulator of major physiological processes, the pituitary gland is a highly dynamic organ, capable of responding to hormonal demand and hypothalamic influence, through adapting secretion as well as remodelling cell numbers among its seven populations of differentiated cells. Stem cells of the pituitary have been shown to actively generate new cells during postnatal development but remain mostly quiescent during adulthood, where they persist as a long-lived population. Despite a significant body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Pituitary hormone deficiencies, which include congenital hypopituitarism (combined pituitary hormone deficiencies), acquired hypopituitarism (secondary to trauma, surgery, chemotherapy, or radiotherapy), as well as pituitary tumors such as adenomas, result in a severe disruption of endocrine systems that could be addressed with PSC therapy ( Castinetti et al, 2011 ). Previous mouse studies demonstrated the existence of PSCs and their ability to self-renew and differentiate into all five endocrine cell types ( Andoniadou et al, 2013 ; Rizzoti et al, 2013 ), thus opening potential therapeutic avenues for human pituitary deficiencies and pituitary tumors ( Russell et al, 2018 ; Vankelecom, 2016 ). Little is known about the epigenetic landscape (chromatin changes as measured by chromatin accessibility assays) and the dynamics of human PSCs during postnatal life, which is critical information for realizing their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary hormone deficiencies, which include congenital hypopituitarism (combined pituitary hormone deficiencies), acquired hypopituitarism (secondary to trauma, surgery, chemotherapy, or radiotherapy), as well as pituitary tumors such as adenomas, result in a severe disruption of endocrine systems that could be addressed with PSC therapy ( Castinetti et al, 2011 ). Previous mouse studies demonstrated the existence of PSCs and their ability to self-renew and differentiate into all five endocrine cell types ( Andoniadou et al, 2013 ; Rizzoti et al, 2013 ), thus opening potential therapeutic avenues for human pituitary deficiencies and pituitary tumors ( Russell et al, 2018 ; Vankelecom, 2016 ). Little is known about the epigenetic landscape (chromatin changes as measured by chromatin accessibility assays) and the dynamics of human PSCs during postnatal life, which is critical information for realizing their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies targeted rodent species and revealed that Sox2 + adult stem/progenitor cells are located within two types of niches: the marginal cell layer lining the pituitary cleft, and the cell clusters scattered in the anterior lobe parenchyma (16,19,25,32). A similar organization of stem/ progenitor cell niches was also suggested in humans (11,31,33,34) and cattle (35,36) by analyzing the expression of SOX2 and other candidate markers. Moreover, a clonogenic cell population, which expresses LHX3 and which can differentiate into prolactin + cells, was isolated from normal human pituitaries from autopsies (age 51-83) (12), supporting the existence of functional stem/progenitor cells in the human pituitary gland throughout life.…”
Section: Pitx1 and Lhx3)mentioning
confidence: 86%
“…Our sorting method could also enrich PITX1 + /LHX3 + pituitary progenitor cells. This cell group was found to express SOX2, which is considered the most common marker for pituitary stem/progenitor cells (30,31), even after 6 months of organoid culture (Figure 2G). To date, much effort has been made to identify stem/progenitor cell populations in the mature pituitary gland (30).…”
Section: Pitx1 and Lhx3)mentioning
confidence: 98%
“…Life events such as stress, puberty and pregnancy-lactation cause remodelling of the AP to allow appropriate levels of hormone production, and changes in cell number and gland size (Perez-Castro et al 2012). Since the stem cell capacity of SRY-related HMG-box 2 expressing (SOX2+) tissue-resident pituitary stem cells (PSCs) was demonstrated (Andoniadou et al 2013; Rizzoti, Akiyama, and Lovell-Badge 2013), many teams have integrated knowledge of developmental signalling pathways with information about their determination and maintenance (reviewed (Russell, Lodge, and Andoniadou 2018)). Importantly, the SOX2+ compartment acts not only as a source of cellular progenitors, but also in postnatal life directs the expansion of more committed cells by the production of paracrine signals, including WNT ligands (Russell et al 2021).…”
Section: Introductionmentioning
confidence: 99%